Conceptual art patterns in cinema (Al-Academy, 2025)
The idea is the tool that makes art, as it rises above the form, so the work becomes a creative process like philosophy, determined by debate and the questioning. Here, the connection between the recipient and the function of art is broken, and the visual perception is employed with the senses, and freedom from the restrictions of formal craftsmanship is achieved, as the conceptual work goes beyond transforming reality and formulating it anew in artistic ways in absolute beauty. Therefore, reality is viewed as the primary field for aesthetic confrontation, i.e. containing a minimum of beauty, and transforming the work from content to concept, i.e. freedom from restrictions.The research deals in its multiple chapters with the methodological framework represented by (the research problem, importance, objectives and limits) and identifying the term conceptualism in defining terms, while in the second chapter the researchers deal with the theoretical framework in several topics (1- Marcel Duchamp, the starting point of conceptual art, 2- Theater of the Absurd, the starting point of rebellion, 3- Cinema as a framework for intellectual models, 4- Contemporary trends) to come out with a list of the types of conceptual art in cinema and deals with a research sample for analysis, which is the film (Mother), produced in 2017. At the end of the research, the researchers came out with results and conclusions through what was presented in the research